2017
DOI: 10.1007/s40505-017-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Assignment games with externalities revisited

Abstract: We study assignment games with externalities. The value that a firm and a worker create depends on the matching of the other firms and workers. We ask how the classical results on assignment games are affected by the presence of externalities. The answer is that they change dramatically. Though stable outcomes exist if agents are "pessimistic", this is a knife-edge result: we show that there are problems in which the slightest optimism by a single pair erases all stable outcomes. If agents are sufficiently opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In markets with externalities, the utility of a user depends not only on the shared resources with its matched user but also generally depends on the existing matching [11]. The main difficulty in dealing with externalities lies in the fact that the core of a cooperative game might be empty in the presence of externalities [33]. Furthermore, the very concept of stability and of blocking pairs is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…In markets with externalities, the utility of a user depends not only on the shared resources with its matched user but also generally depends on the existing matching [11]. The main difficulty in dealing with externalities lies in the fact that the core of a cooperative game might be empty in the presence of externalities [33]. Furthermore, the very concept of stability and of blocking pairs is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Since Shapley and Shubik [1972], where cooperative assignment games associated with assignment problems were introduced, different generalizations have been developed. Three of these extensions are quasi-assignment games [Auriol and Marchi, 2002], infinite assignment games [Llorca et al, 2004] and assignment games with externalities [Eriksson et al, 2011;Gudmundsson and Habis, 2017]. Quasi-assignment games are assignment games in which some inequalities are converted into equalities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also proposed a weak stability concept that allows a pair of agents to block a matching only if they benefit from the block under all possible rematches of the remaining agents and showed that such weak stable matchings exist in one-to-one environments. Much of the subsequent literature-e.g., Chowdhury (2004); Hafalir (2008); Eriksson, Jansson and Vetander (2011); Chen (2013); Gudmundsson and Habis (2017); Salgado-Torres (2011a,b); Bodine-Baron et al…”
mentioning
confidence: 99%